Влијанието на пораките пренесени преку социјалните мрежи врз намерите за он-лајн купување - Матевска Перовска, Фани (Економски факултет, УКИМ, Скопје, 2021)
Word of mouth communication (WOM) is a marketing tool with a primary purpose for communication and socialization, as well as promotion and sale of products, that takes place face to face, between sellers and buyers. With the advent of the Internet, WOM has transformed into eWOM, that is electronic word od mouth communication, which takes place between online sellers and online buyers through social networks and online store websites. Consumers can exchange online messages, experiences, comments and leave rated reviews for products that they have already purchased on-line. This new way of eWOM communication has great potential to influence on-line shopping intentions. In this context, the purpose of this doctoral dissertation is to analyze and explore the impact of eWOM communication on on-line purchase intentions. The quality and the credibility of messages, the consumers`needs and attitudes towards messages, the usefulness and the acceptance of messages by on-line consumers, are analyzed as determinants of on-line messages that can be transmitted through social networks and websites of online stores. Тhe determinants of on-line messages are derived from the Informaton Acceptance Model based on Consumers` Needs and Attitudes (IACM). IACM is the research model of this doctoral dissertation, based on which the impact of on-line messages on consumers` purchase intentions, is analyzed. Finally, an analysis of the two on-line platforms of eWOM communication was performed, by using adequate statistical methods, in order to determine, whether the messages transmitted through the Facebook pages of the online stores have greater impact on the on-line consumers` purchase intentions than the messages that are transmitted through the on-line websites` communication tools or vice versa. The results of the research give useful conclusions for marketers, in order to adapt their online marketing strategies for successful Facebook and web site on-line promotions and sales.
The influence of electronic word of mouth through social networks on consumers’ on-line purchase intentions
Докторска дисертација одбранета во 2021 година на Економскиот факултет во Скопје, под менторство на проф. д–р Сашо Јосимовски.
Keywords: eWOM, on-line purchase intentions, social media networks, on-line stores